1991
DOI: 10.1002/path.1711640105
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral nerve sheath tumour with annulate lamellae mimicking pleomorphic malignant fibrous histiocytoma

Abstract: The nature and nosologic status of malignant fibrous histiocytoma (MFH), or at least its most common pleomorphic variant, are a matter of controversy and it is possible that this entity represents the shared morphologic phenotype of a range of other dedifferentiated neoplasms. An unusual case of malignant peripheral nerve sheath tumour which very closely mimicked pleomorphic MFH is presented. Its true nature was only disclosed by ultrastructural examination. A further interesting and previously unreported feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some of these fragments contained several profiles of endoplasmic reticulum, as well as ring-shaped annulate lamellae. The presence of annulate lamellae in these cytoplasmic fragments may indicate that they were parts of hyperplastic cells, since several studies revealed the presence of these unique structures in carcinoma cell lines and malignant tumors (Goodlad and Fletcher, 1991;Mirejovsky, 1991;Ueda et al, 1991;Wang et al, 1992;Pettinato et al, 1993). These lamellae are considered to be derived from the outer lamellae of the nuclear membranes or from the intracytoplasmic endoplasmic reticulum (Johannessen, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these fragments contained several profiles of endoplasmic reticulum, as well as ring-shaped annulate lamellae. The presence of annulate lamellae in these cytoplasmic fragments may indicate that they were parts of hyperplastic cells, since several studies revealed the presence of these unique structures in carcinoma cell lines and malignant tumors (Goodlad and Fletcher, 1991;Mirejovsky, 1991;Ueda et al, 1991;Wang et al, 1992;Pettinato et al, 1993). These lamellae are considered to be derived from the outer lamellae of the nuclear membranes or from the intracytoplasmic endoplasmic reticulum (Johannessen, 1979).…”
Section: Discussionmentioning
confidence: 99%